Growth in the Central and Eastern European Countries of the European Union - Abiad, Abdul (Occasional Papers; Occasional Paper ;, 2007)
The central challenges facing the Czech Republic, Estonia, Hungary, Latvia, Lithuania, Poland, Slovakia, and Slovenia as they work to catch up to advanced European Union (EU) income levels are discussed in this new book. Focusing on the region's growth performance, and outlining two growth scenarios that illustrate the range of investment and productivity growth rates under the income catchup objective, the authors draw upon extensive resources to identify strengths and weaknesses.